Penerapan Bimbingan Individu Dalam Membaca Al-Qur’an Dengan Metode Ummi Di TPQ/TKQ Al-Huda Kec. Sukarame Palembang - Jeki Ariwibowo; Anang Walian; Kusnadi (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This research is entitled "Implementation of Individual Guidance in Reading the Al-Qur'an using the Ummi Method at TPQ/TKQ Al-Huda District. Sukarame Palembang.” This type of research uses a qualitative approach by conducting a survey of the object being studied. This type of qualitative data aims to explain how individual guidance is applied in reading the Al-Qur'an using the Ummi method at TPQ Al-Huda, and how effective the application of individual guidance is in reading the Al-Qur'an using the Ummi method at TPQ Al-Huda. This research was motivated by the author's observations and interviews with students who had difficulty learning to read the Koran. And this is made worse by the ustadz who teach not using good methods in teaching reading the Koran to students. So there are some students who cannot complete learning to read the Koran and are left behind by other students. As a result, these students feel inferior to their friends and show poor learning behavior. Of course, this is not in accordance with TPQ Al-Huda's vision, namely preparing the Qur'anic generation, in order to face a glorious future. Therefore, the author is interested in conducting research at one of the TPQ/TKQ located in Sukarami District, Palembang City, specifically at TPQ/TKQ Al-Huda which is located at Jalan Cempaka II No. 3122 Rt. 021 Rw. 004 Sukodadi Village, Sukarami District, Palembang. The results of this research are that the application of individual guidance in reading the Al-Qur'an using the Ummi method at TPQ/TKQ Al-Huda on average has quite satisfactory and good results. The percentage of students' learning behavior is 64% good, 36% sufficient, and 0% poor. Then for the written test on the science of recitation, the average minimum score for students reaches 80 and the same goes for the oral test score on reading the Al-Qur'an with an average score of at least 80 with a percentage of 100% complete. Meanwhile, the effectiveness of implementing individual guidance in reading the Al-Qur'an using the Ummi method has had a positive impact and influence and succeeded in achieving the desired goal, namely in the form of completeness in students' learning which has reached 100%.